Sponsored Content on Instagram as an Effort to Increase Promotional Effectiveness in Digital Advertising: A Systematic Review of the Literature - Diana Siti Rahmawati; Marsaa Salsabila Syawal; Ari Andriano Santoso (International Journal Labs, 2025)
The rapid growth of social media use in Indonesia, especially Instagram, has transformed digital advertising strategies, with sponsored content emerging as a key promotional tool. Sponsored content, often delivered by influencers via stories and feeds, is perceived as more authentic and engaging compared to conventional brand ads. However, concerns about the transparency and ethical disclosure of sponsored content persist, affecting consumer trust and regulatory practices. This study aims to systematically review the effectiveness and characteristics of sponsored content on Instagram as a promotional medium in digital advertising, focusing on both global insights and implications for Indonesia. A systematic literature review (SLR) was conducted, analyzing 19 journal articles published between 2019 and 2023 sourced from databases including Scopus, Google Scholar, Sage Journals, and Taylor & Francis. The review applied PRISMA guidelines for identification, screening, and inclusion of relevant studies. Findings reveal that influencer-sponsored content on Instagram enhances brand awareness, consumer engagement, and purchase intent more effectively than traditional ads. Disclosure of sponsorship is crucial to prevent audience confusion and build trust, with regulations established in regions like Europe and America. Nonetheless, limited research addresses the Indonesian context, indicating a gap in understanding local practices and regulatory frameworks. This review highlights the need for future research exploring sponsored content within Indonesia’s digital advertising landscape and calls for the development of clear consumer protection policies to ensure transparency and ethical promotion on social media platforms..